2022
DOI: 10.3390/diagnostics12112764
|View full text |Cite
|
Sign up to set email alerts
|

IDH Mutations Are Potentially the Intrinsic Genetic Link among the Multiple Neoplastic Lesions in Ollier Disease and Maffucci Syndrome: A Clinicopathologic Analysis from a Single Institute in Shanghai, China

Abstract: Background: This study aims to investigate isocitrate dehydrogenase gene mutations in patients with the non-hereditary skeletal disorders of Ollier disease and Maffucci syndrome, particularly in the extraosseous tumours. Methods: A total of 16 tumours from three patients with Ollier disease and three patients with Maffucci syndrome were collected. Sanger sequencing was applied to determine the hotspot mutations of IDH1 and IDH2 genes in multiple neoplastic tissues. Results: A majority of the tumours displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…The pathogenesis of Maffucci syndrome is currently unclear, but it is generally believed to be caused by non-hereditary mutations in IDH1 and IDH2 ( 1 , 7 , 8 ). Amary et al ( 1 ) and Pansuriya et al ( 8 ) reported that Maffucci syndrome is caused by somatic mosaic IDH1/2 mutations, which can also be related to cases of isolated enchondroma and chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of Maffucci syndrome is currently unclear, but it is generally believed to be caused by non-hereditary mutations in IDH1 and IDH2 ( 1 , 7 , 8 ). Amary et al ( 1 ) and Pansuriya et al ( 8 ) reported that Maffucci syndrome is caused by somatic mosaic IDH1/2 mutations, which can also be related to cases of isolated enchondroma and chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Вторинним центральним ХС притаманне розширене ендостальне гребінчасте ураження, ремоделювання кіркового шару, його деструкція та періостальна реакція на рентгенограмах, особливо в порівнянні з попередніми зображеннями основної енхондроми [72,73]. На КТ-сканах характерними ознаками злоякісного новоутворення є літичні ділянки, ендостальний фестон на 2/3 кортексу та більше або поширення на м'які тканини [72].…”
unclassified